Youth of the Russian Far East lead in the fight against climate change - Sorokin, Maksim (2023)
The United Nations has emphasised the indispensable role of young people in preserving the earth’s environment and sustaining the ecology of the planet. In this respect, youth activism across the Russian Far East is contributing to increased public awareness on environmental and ecological concerns, especially regarding climate change issues and the mitigation actions needed. More effort must be exerted to deal with the looming climate crisis.